2013
DOI: 10.1002/jctb.4195
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced synergistic influence of mixed substrate cultivation on single step copolymer P(3HB-co-4HB) biosynthesis with a wide range of 4HB monomer composition

Abstract: BACKGROUND: Copolymer poly(3-hydroxybutyrate-co-4-hydroxybutyrate), P(3HB-co-4HB) has gained importance in biotechnological processes due to its potential as an absorbable material in biopharmaceutical applications. The aim of the present study was to investigate the implementation of mixed substrate cultivation concept in single step production of copolymer P(3HB-co-4HB). Evaluation of the sole carbon sources was first carried out to elucidate the difference in the monomer content of 4HB using different types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
2
14
0
4
Order By: Relevance
“…In other words, our findings suggest that different substrate combinations and concentrations exerted more influence on the molecular weight. This assertion is supported by our previous report in shake-flask fermentation [12]. However, in the case of the substrate mixture of γ + 1,6 and 1,4 + 1,6, when both the carbon sources in the substrate mixtures were supplied at medium concentration level (M γ +M 1,6 and M 1,4 + M 1,6 ), the M w and M n values were the lowest as compared to the combination of different concentration levels.…”
Section: Molecular Weight Distribution and Polymer Randomnesssupporting
confidence: 89%
See 1 more Smart Citation
“…In other words, our findings suggest that different substrate combinations and concentrations exerted more influence on the molecular weight. This assertion is supported by our previous report in shake-flask fermentation [12]. However, in the case of the substrate mixture of γ + 1,6 and 1,4 + 1,6, when both the carbon sources in the substrate mixtures were supplied at medium concentration level (M γ +M 1,6 and M 1,4 + M 1,6 ), the M w and M n values were the lowest as compared to the combination of different concentration levels.…”
Section: Molecular Weight Distribution and Polymer Randomnesssupporting
confidence: 89%
“…It was concluded that in single-stage cultivation, the bacterium has the ability to accumulate high PHA content with lower 4HB molar fraction [1]. However, in our recent report we demonstrated that the shake-flask scale research has not only revealed its potential in improving the copolymer accumulation, but it has also resulted in the accumulation of a wide range of 4HB monomer, ranging from 7 to 70 mol% [12]. This is a breakthrough study on single-stage biosynthesis of copolymer P(3HB-co-4HB), which resulted in the increase in monomer composition by using mixedsubstrate cultivation strategy.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 79%
“…The P(3HB‐ co ‐4HB) is a short‐chain‐length polyhydroxyalkanoate ( scl ‐PHA) which is like other PHAs, being produced under nutrient limited condition but with an excess carbon sources. It can be produced by various types of bacterial species such as Alcaligenes latus, Comamonas acidovarans, Cupriavidus necator and Hydrogenophage pseudoflava , with the addition of 4HB precursors such as γ‐butyrolactone, 1,4‐butanediol, 1,6‐hexanediol and 1,8‐octanediol . This 4HB‐incorporated thermoplastic has been reported to be a promising biomaterial, either in bio‐pharmaceutical application as the excipient in drugs or as wound dressing in medical application .…”
Section: Introductionmentioning
confidence: 99%
“…The P(3HB-co-4HB) is a short-chain-length polyhydroxyalkanoate (scl-PHA) which is like other PHAs, being produced under nutrient limited condition but with an excess carbon sources. It can be produced by various types of bacterial species such as Alcaligenes latus, Comamonas acidovarans, Cupriavidus necator and Hydrogenophage pseudoflava, with the addition of 4HB precursors such as γ-butyrolactone, 1,4-butanediol, 1,6-hexanediol and 1,8-octanediol [1][2][3][4]. This 4HB-incorporated thermoplastic has been reported to be a promising biomaterial, either in Correspondence: Prof. A.A. Amirul (amirul@usm.my) School of Biological Sciences, Universiti Sains Malaysia, 11800 Minden, Penang, Malaysia Abbreviations: NaOH, Sodium hydroxide; NPCM, Non-polymeric cell material digestion; PHA, Polyhydroalkanoate; P(3HB-co-4HB), Poly(3-hydroxybutyrate-co-4-hydroxybutyrate); RSM, Response surface methodology bio-pharmaceutical application as the excipient in drugs [5] or as wound dressing in medical application [6].…”
Section: Introductionmentioning
confidence: 99%
“…Біосинтез інших мікробних метаболітів на змішаних субстратах. Стратегія використання суміші субстратів використовується не лише для отримання ПАР, а й для інших практично цінних мікробних метаболітів: ліпідів [16][17][18][19][20][21][22][23][24], екзополісахаридів [25][26][27], пілігідроксиалканоатів [28][29][30], ферментів [31][32][33], органічних кислот [34][35][36][37][38], пропандіолу [39,40], біоетанолу [41], біоводню [42,43].…”
unclassified